Hyperbranched aliphatic polyether esters by ring‐opening polymerization of epoxidized 2‐hydroxyethyl methacrylate. Issue 12 (15th April 2014) - Huang, Xinhua; Heo, Min Seon; Yoo, Jin‐Wook; Choi, Jin‐Seok; Kim, Il
ABSTRACT A series of biocompatible and degradable hyperbranched polyether esters, poly(2‐hydroxyethyl 2‐methyloxirane‐2‐carboxylate) (pHEMOC) with controlled molecular weight (MW) and polydispersity (PD), have been synthesized via oxyanionic ring‐opening polymerization of HEMOC that was prepared by the epoxidation of 2‐hydroxyethyl methacrylate. pHEMOCs of their MWs ranging from about 500 to 20, 000 with their PD values less than 1.5 are obtained simply by controlling 1, 1, 1‐tris‐hydroxymethylpropane initiator to HEMOC ratio. The pHEMOCs comprised of ether and ester backbones and multiple hydroxyl groups on the core and periphery results in materials that exhibit good degradability and low cytotoxicity, enabling them to be an ideal candidate material for biomedical applications. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1643–1651